Syntactic Error Analysis in High School Students’ Scientific Writing - Ratnani, Nabilla Yhusri; Markamah, Markamah; Sabardila, Atiqa (FKIP - Universitas Riau, 2026)
Syntactic errors in students’ scientific writing (KTI) remain a common issue that affects the clarity and effectiveness of academic communication. This study aims to analyze the types of syntactic errors in students’ scientific writing and to describe the implementation of Problem-Based Learning (PBL) in Indonesian language learning. The research employed a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and document analysis of eleventh-grade students’ scientific papers. Data analysis used an interactive analysis model, while error analysis techniques included identification, classification, and description of syntactic errors. The results show that various types of syntactic errors were found, including diction errors, unclear sentences, ambiguous sentences, redundant sentences, inappropriate loanwords, coherence errors, non-standard sentences, and pleonasm. The most dominant errors were diction errors and unclear sentence structures, indicating that students still experience difficulties in constructing effective and grammatically correct sentences. In conclusion, the implementation of PBL provides a supportive learning context that encourages systematic thinking, collaborative discussion, and revision processes, which contribute to improving students’ writing quality.